Avaliação da potência neutralizante de antivenenos loxoscélicos através do uso de proteínas recombinantes do veneno de Loxosceles sp e avaliação do potencial imunoprotetor de uma proteína quimérica multiepitópica - Natália Alves Souza Carvalhais (2018)
Accidents with venomous animmals represent a health issue in Brazil, and the brown spider’s accidents are pointed out as the second most frequent ones. The accidental envenomation by brown spiders (Loxosceles sp.) cause a strong local dermonecrotic effect which can be followed by systemic manifestations, and even though the systemic loxoscelism occurs in a small portion of the cases, it can be fatal. The production of antivenoms for the treatments of such accidents relies on a variety of animal experiments, from the spider venom extraction to the production of antivenom in horses and its in vivo neutralizing potency evaluation, which is performed in rabbits. In the present work, there is an attempt to reduce and optimize animal experiments with two different approaches. The first approach relies in the construction and production of a chimeric protein, named Lil, containing immunodominant epitopes that were previously mapped from the main protein of the Loxosceles venom, the Sphingomyelinase D. The Lil protein contains epitopes from Sphinomyelinases D of the three main species found in Brazil. The Lil protein was found capable of inducing antibodies with the potential to partialy neutralize the toxic effects of Loxosceles intermedia venom in an animal model. Therefore, in order to reduce spider usage and to provide a less harmfull life to the horses used for immunization we suggest the Lil protein as a potential candidate to replace the venom usage in the antivenom production protocols. The second approach was to elaborate an in vitro test for the distinction of high and low potency sera. The Loxosceles laeta Smase I was able to correctly diagnose the neutralizing potency of the evaluated sera, in an ELISA test. Thus, we suggest the use of such test as means to discriminate the neutralizing potency of the antiloxosceles sera as an alternative to the in vivo protocols relying on rabbits.